Модель трафика ETHERNET в виде ON/OFF процесса - Роздымаха, Е. А.; Омельченко, А. В.; Федоров, А. В. (ХНУРЭ, 2011)
A model of fractal traffic based on the on/off model has been considered. A way to estimate mean queue length in a buffer of telecommunication equipment that is necessary to serve traffic properly has been suggested.
Keywords: трафик; сети с коммутацией пакетов